2020
DOI: 10.1186/s12974-020-01897-z
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin facilitates peripheral nerve regeneration through regulating M1/M2 switching

Abstract: Background: Excessive inflammation within damaged tissue usually leads to delayed or insufficient regeneration, and nerves in the peripheral nervous system (PNS) generally do not recover fully following damage. Consequently, there is growing interest in whether modulation of the inflammatory response could help to promote nerve regeneration in the PNS. However, to date, there are no practical therapeutic strategies for manipulating inflammation after nerve injury. Thrombomodulin (TM) is a transmembrane glycopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Pro-inflammatory responses in the conduit of nerve segment were induced after 6-week post-injury in the nerve transection and silicone conduit sutured rats [ 26 , 33 ]. We observed that PBA had a beneficial effect on the inhibition of pro-inflammatory cytokines in vitro; therefore, we investigated the therapeutic potential of PBA for the modulation of inflammation in the nerve conduit after sciatic nerve transection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pro-inflammatory responses in the conduit of nerve segment were induced after 6-week post-injury in the nerve transection and silicone conduit sutured rats [ 26 , 33 ]. We observed that PBA had a beneficial effect on the inhibition of pro-inflammatory cytokines in vitro; therefore, we investigated the therapeutic potential of PBA for the modulation of inflammation in the nerve conduit after sciatic nerve transection.…”
Section: Resultsmentioning
confidence: 99%
“…The conductive microenvironment was investigated by studying the level of nerve innervation to the targeted gastrocnemius muscle as an indicator of the successful regeneration outcome [ 26 , 33 ]. The degree of nerve reinnervation was analyzed by determining the relative gastrocnemius muscle weight (RGMW) and performing a histological examination using cross-sectional image of innervated muscle tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β and TNF-a are important inflammatory cytokines. Studies have shown that nerve injury can lead to an increase in the level of IL-1β and TNF-a, while reducing their release can reduce the inflammatory response of the nerve, which is beneficial to the repair of nerve injury ( Huang et al, 2020 ; Wang et al, 2020 ). Therefore, we investigated the changes in IL-1β and TNF-a in rat serum after NSC and MC-NSC transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Among these cytokines, induction of PDGF and IFN-α by zymosan stimulation has been demonstrated in macrophages and dendritic cells, respectively [43,44]. In addition, recent data suggest that the membrane-associated proteins, including ATP-binding cassette transporter A1, thrombomodulin, and Annexin A1, are involved in STAT6/PPARγ signaling pathway [45][46][47][48]. Thus, further investigation is needed to determine whether and how these proteins participate in this pathway during zymosan-induced peritonitis.…”
Section: Discussionmentioning
confidence: 99%